Developing and applying the board game 'caminhando pelo sus': an experience report - Guilherme Raffo Wachholz; Robson Miguel Arrosi; Clarissa De Antoni (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2019)
Programa de Iniciação à Docência (PID) stimulates the development of new active learning methodologies, integrating both teachers and students. In health literature, researchers have questioned traditional pedagogical models, since them can make the students passive to their own learning process. The purpose of this article is to report the development process of a board game, named 'Caminhando pelo SUS', to be used as a learning method. The game contains one board, 55 cards, 4 pins and one manual, and the main purpose is to reach the final house on the board. In order to advance in the game, the player must answer correctly the questions related to its content. The game has been proving to be a helpful active learning methodology, since its dynamics can stimulate the students in a autonomous and proactive way through their learning process.